Pathophysiologic Approach to Pain Therapy for Complex Pain Entities: A Narrative Review - Rekatsina, Martina (Pain Ther, 2020)
Pain management is challenging for both clinicians and patients. In fact, pain patients are frequently undertreated or even completely untreated. Optimal treatment is based on targeting the underlying mechanisms of pain and tailoring the management modality for each patient using a personalized approach. This narrative review deals with pain conditions that have a complex underlying mechanism and need an individualized and frequently multifactorial approach to pain management. The research is based on previously conducted studies, and does not contain any studies with human participants or animals performed by any of the authors. This is not an exhaustive review of the current evidence. However, it provides the clinician with a perspective on pain therapy targeting the underlying pain mechanism(s). When dealing with complex pain conditions, the prudent physician benefits from having a deep knowledge of various underlying pain mechanisms in order to provide a plan for optimal pharmacological pain relief to patients.